Road maintenance seminar funding and financial management : delegate information, Thursday 24 June 1999, Viking Moat House Hotel, York (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in York on 24 June 1999.